2018
DOI: 10.1111/ijfs.13954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential use of discard species for fish silage and assessment of its oils for human consumption

Abstract: Waste or by-products contains a substantial amount of nutrients. Fish silage is an alternative way for assessment of fish discards and waste generated in the fish processing industries. The aim of the study was to evaluate the potential use of discard species (Equulites klunzingeri, marine fish and Carassius gibelio, freshwater fish) for fish silage and chemical quality of fish oil extracted from fish silages prepared with acid and fermented methods. Lipid quality of fish oils extracted from fish silages with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…4F and 5E). Thus, if ensilaging is done >22 °C, it is important that the correct oxidation markers are used if aiming at a high quality fish silage and/or at extracting high-quality oils for feed or human consumption 26 . For the latter, lipid oxidation should be kept within the acceptable limits for edible oils set by the GOED Voluntary Monograph 59 .…”
Section: Optimization Of the Ensilaging Processmentioning
confidence: 99%
“…4F and 5E). Thus, if ensilaging is done >22 °C, it is important that the correct oxidation markers are used if aiming at a high quality fish silage and/or at extracting high-quality oils for feed or human consumption 26 . For the latter, lipid oxidation should be kept within the acceptable limits for edible oils set by the GOED Voluntary Monograph 59 .…”
Section: Optimization Of the Ensilaging Processmentioning
confidence: 99%
“…Different fish forms can also be utilised to enhance the nutritional value of various foods (Desai et al ., 2019). It has been reported that even the oils recovered from fish by‐product or waste can be a good source of nutrition due to their polyunsaturated fatty acid content (Özyurt et al ., 2019). Consumption of fish has been shown to reduce the risk of coronary heart disease, decreases mild hypertension and prevents certain cardiac arrhythmias (Sidhu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of discard or by‐products of seafood processing as animal feed has been demonstrated to be economically viable since it is not only a method of waste disposal but also an alternative for feeding livestock. The use and disposal of product waste are challenging because of its inadequate biological stability, high water content, high potential for rapid auto‐oxidation, potentially pathogenic nature, and high level of enzymatic activity (Özyurt, Özkütük, et al, 2019; Özyurt, Ozogul, et al, 2019). Therefore, the production of fish hydrolysates has a promising potential to produce high‐quality animal feed and disposal of fish discards and by‐product.…”
Section: Resultsmentioning
confidence: 99%